Pengaruh Penanganan Keluhan dan Komunikasi Pemasaran Terhadap Loyalitas - Muhammad Ade Kurnia Harahap; Normansyah Normansyah; Siti Nurhayati; Irma M Nawangwulan; Samuel PD Anantadjaya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
Customer loyalty is one of the most important aspects in the business world. Retaining existing customers is often more cost-effective than finding new customers. The purpose of this study was to analyze the effect of complaint handling and marketing communication on loyalty. The research method used is a literature study or Library Research with a qualitative approach. Based on the literature review conducted on the results and discussion, it can be concluded as follows: (1) The effect of handling complaints has a positive effect on loyalty (2) The effect of marketing communication has a positive effect on loyalty. Keywords: complaint handling, marketing communication, loyalty